EVALUASI SISTEM INFORMASI AKUNTANSIPENERIMAAN DAN PENGELUARAN MATERIAL PADA PT.PRIMA SEJATI SEJAHTERA (PRIMA 3) BOYOLALI - Rinjani, Suryaningrum Ayu; W., Endang Masitoh; Wijayanti, Anita (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
This study aims to determine the accounting information system of material receipts and expenses at PT. Prima sejati sejahtera. The method used is by using descriptive analysis techniques andverification. This type of research is qualitative research. This research is in the form of data that is not based on numbers but based on documents or proof of transaction. The data obtained is directly related to theories. Based on the results of the research for accounting information systems included in the category good. Qualitative research is a research approach that uses data that is measured indirectly, such as activities, attitudes, sentences, words, pictures, and so on. The research process takes into account the context of the study by focusing on understanding, thinking and perceptions of research.